REVIEW ARTIKEL : ANALISIS KANDUNGAN ASAM ASKORBAT PADA BEBERAPA TANAMAN - Lukman, Hilmia; Shofia, Vivi (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2023)
Ascorbic acid or vitamin C is an essential organic compound for the body and has many health benefits. Vitamin C cannot be produced by the body, so it must be obtained from outside the body through food consumption. The vitamin C in plants varies considerably depending on the type, the part of the plant, and the growing environment. Vitamin C analysis can be carried out using qualitative and quantitative methods. This article review aims to review qualitative and the quantitative analysis of vitamin C using plant samples. The plants used in the study are plants that are widely consumed in Indonesia, namely matoa fruit (Pometia pinnata), water spinach (Ipomoea reptana Poir), spinach (Amaranthus spinosus), cucumber (Cucumis sativus L.), enau fruit (Arenga pinnata Merr.) and katuk leaves (Sauropus Androgynus). The qualitative analysis of vitamin C used FeCl3, KMnO4, Methylene blue and AgNO3 reagents, while the qualitative analysis uses the UV-Vis spectrophotometry method and several titration methods.